1990
DOI: 10.1193/1.1585583
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of the 1985 Michoacan Earthquake on the Water Systems in Metropolitan Mexico City

Abstract: During the Michoacan earthquake of September 19, 1985, the water supply and distribution systems of Metropolitan Mexico City were severely damaged. This paper investigates the type of damage, taking into consideration the characteristics of the earthquake and the peculiar soil and topographic conditions of the valley where the city is situated. It describes the water systems in the metropolitan area, the main features of the subsoil conditions and the engineering aspects of the earthquake, highlighting their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…A comprehensive recognition of the damage was done by Ayala and O'Rourke (1989), where three conclusions were presented: 1) the damage was mainly due to seismic wave propagation; 2) the accumulated ground subsidence in the Valley of Mexico could have increased the damage; and 3) the spatial location ofthe network in the lake zone, characterized by clay sediments, increased the damage to the system due to propagation of seismic waves.…”
Section: Pgvz/pga As Seismic Damage Predictor For Pipelines Located Imentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive recognition of the damage was done by Ayala and O'Rourke (1989), where three conclusions were presented: 1) the damage was mainly due to seismic wave propagation; 2) the accumulated ground subsidence in the Valley of Mexico could have increased the damage; and 3) the spatial location ofthe network in the lake zone, characterized by clay sediments, increased the damage to the system due to propagation of seismic waves.…”
Section: Pgvz/pga As Seismic Damage Predictor For Pipelines Located Imentioning
confidence: 99%
“…For the case of Mexico City, three things contributed to find a better damage predictor for the Mexico City Water System in comparison to PGV alone: 1) the research advances made mainly after the 1985 earthquake that have contributed to better understand and measure seismic ground motion in Mexico City; for example, the PGV ground motion maps proposed by Pineda and Ordaz (2004) were used to compute the fragility functions proposed by Pineda and Ordaz (2003), and later for creating the PGV2/PGA-based fragility functions of Pineda and Ordaz (2007). 2) The comprehensive damage scenario for the Mexico City's Water System, due to the 1985 earthquake, done by O'Rourke and Ayala (1989). And, 3) the linear fragility relationship proposed by Pineda and Ordaz (2007) that demonstrate that pipe repairs are directly related to PGV2/PGA.…”
Section: Future Challenges For Developing Enhanced Pipeline Fragilitiesmentioning
confidence: 99%
“…A detailed PGV map is used to find the best relationship between repair rate and seismic intensity. The results showed that a PGV-based fragility relation is the best option for Mexico City's water system [15].…”
mentioning
confidence: 92%
“…The MCWS was severely affected by the 1985 earthquake, causing extensive damage that left around 40% of the 8.5 million people living in the Federal District without water service. A comprehensive report on the damage was published by Ayala and O'Rourke M. (1989). They observed that two-thirds of the damage was located at pipe joints; and that the observed failure types include lateral crushing of pipes, and crushing and unplugging of joints.…”
Section: Description Of the Mcws And Its 1985 Damage Scenariomentioning
confidence: 99%
“…In order to reduce the uncertainty in the damage estimation for the MCWS, in this study only two fragility functions Ordaz, 2003 and2007) are used to estimate the damage in the pipeline system. Pineda and Ordaz (2003) proposed a fragility formulation for buried pipelines employing the 1985 damage scenario published by Ayala and O'Rourke M. (1989), and the detailed maps for Mexico City proposed by Pineda and Ordaz (2004). In order to analyze the variability of the relationship between damage rates (rep/km) and PGV for several ranges of seismic intensity, nine scenarios were used to generate a PGV-based fragility function.…”
Section: Seismic Fragility Functions Based On the 1985 Mcws Damage Scmentioning
confidence: 99%